2022
DOI: 10.1080/0886022x.2022.2048856
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hypocalcemia in dialysis patients with refractory secondary hyperparathyroidism after parathyroidectomy: a meta-analysis

Abstract: Objective Hypocalcemia after parathyroidectomy (PTX) results in tetany, diarrhea, cardiac arrhythmia, and even sudden death. However, a meta-analysis or systematic evaluation of risk factors with the occurrence and development of hypocalcemia in patients with secondary hyperparathyroidism (SHPT) after PTX has never been performed. Methods A thorough search of electronic databases, including PubMed, Web of Science, the Cochrane Library, and EMBASE, was performed to retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Younger age was found to be a preoperative risk factor for SH in this study, which is largely consistent with the previous reports [ 30 , 34 36 , 43 , 44 , 46 ]. Explanation as to why younger patients are at a higher risk of hypocalcemia mainly includes stronger osteoblast function and greater calcium utilization efficiency of bone tissue.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Younger age was found to be a preoperative risk factor for SH in this study, which is largely consistent with the previous reports [ 30 , 34 36 , 43 , 44 , 46 ]. Explanation as to why younger patients are at a higher risk of hypocalcemia mainly includes stronger osteoblast function and greater calcium utilization efficiency of bone tissue.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, preoperative iPTH as one of the risk factors of postoperative hypocalcemia has been frequently found in patients who underwent PTX [ 29 , 31 34 , 36 , 37 , 39 , 40 , 43 , 44 ]. It is well accepted that preoperative iPTH concentration can be used to predict postoperative hypocalcemia, because it is consistent with the physiological functions of iPTH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative management is also crucial for SHPT patients ( 20 , 21 ). This case shows that clinicians need to closely monitor patients' blood calcium to promptly discover and treat hypocalcemia ( 6 , 22 ). In recent years, the mode of multidisciplinary team (MDT) management has been introduced into the treatment of SHPT patients ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, preoperative ALP elevation was found to be a risk factor for postoperative HBS. Gong et al (12), Tsai et al (13) and Gao et al (14) showed in literature that age, preoperative calcium, ALP, and iPTH concentration are associated with HBS. Gong et al (12) reported that advanced age is a risk factor for postoperative HBS, but Jakubauskas et al (15) concluded that the younger the age, the higher the risk of HBS.…”
Section: Discussionmentioning
confidence: 99%